Analysis of Npk in Human Male and Female Urine - Kuwornu, Alfred L. K. (2011)
A Thesis submitted to the Department of Theoretical and Applied Biology, Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the requirements for the Degree of